A laser tomograph technique for ice core stratigraphy analysis - タカタ, モリマサ; フジイ, ヨシユキ; Takata, Morimasa; Fujii, Yoshiyuki (National Institute of Polar Research, 2000)
P(論文) We have developed a laser tomograph system to analyze the detailed stratigraphic structure of ice core samples. We use a He-Ne laser as the light source and a CCD camera as a detector of a scattered image of air bubbles in ice. An image of air bubble distribution in the ice sample is obtained by image analysis of the scattered images. Two different algorithms are employed in the image analysis in order to improve the laser tomograph images. A profile of pore ratios obtained by using optimum conditions and algorithms for the analysis shows a good correlation of 0.80 with the actual pore ratio profile. departmental bulletin paper